The fate of a Military Pilot in Malaysia: Lingering on the ground after young stroke (International Journal of Occupational Safety and Health, 2022)
Strokes in young pilots can result in the devastating loss of productive years of life, especially for pilots at the peak of their careers. A 32-yr-old male military helicopter pilot was diagnosed with superior sagittal sinus thrombosis and bilateral parietal hemorrhages secondary to protein S deficiency after 15 years in military service. Two years post-stroke, he was carefully evaluated for a possible return to work after aeromedical assessment and the 1 percent rule being considered. A decision was made by the medical board for him to be disqualified to fly and grounded with work accommodation. The authors recommend that there is a need for reassessment up to two years using the objective PULHEEMS method for young pilots who failed aeromedical assessment due to stroke for returning to work as their experiences and knowledge is highly valuable.